VIRTUAL INFLUENCER ACTIVITIES ON INSTAGRAM SOCIAL MEDIA THROUGH THE PERSPECTIVE OF USER GENERATED CONTENT THEORY - Naya, Pramedistiyani N Ain; Hidayat, Dasrun; Rina, Nofha; Nurhadi, Zikri Fachrul (Interaksi: Jurnal Ilmu Komunikasi, 2024)
Rapid technological developments have given rise to new technologies, one of which is Artificial Intelligence (AI). Virtual Influencers are a phenomenon that is currently popular in Indonesia. The emergence of virtual influencers is based on the increasingly advanced existing technology. The emerging artificial intelligence has an influence on the marketing of products or services on social media, especially on the Instagram platform. This research aims to determine the virtual activities of influencers on Instagram. The research method used is a descriptive qualitative method that is in-depth on empirical findings containing related information about virtual influencers. Research results obtained from interviews with sources show that virtual influencers are an effective technological advancement in helping a brand market its products or services. Even though most of them received  positive responses, it cannot be denied that virtual influencers also received negative responses. Virtual influencers are considered to be more able to adapt to a brand's wishes. In terms of marketing, virtual influencers  are easier to control because basically behind virtual influencers there are humans who design the program.